Effect of postactivation potentiation on fifty-meter freestyle in national swimmers - Sarramian, V. G.; Turner, A. N.; Greenhalgh, A. K. (The Journal of Strength and Conditioning Research, 2015)
The purpose of this study was to examine the effect of PAP on 50-m freestyle in national-level swimmers. Four warm-ups were compared: a traditional race-specific warm-up (RSWU), upper-body PAP (UBPAP), lower-body PAP (LBPAP), and combined PAP warm-up (CPAP). Eighteen (10 men, 8 women) national-level swimmers participated in this study, which included 7 separate testing sessions. Participants' 3 repetition maximum (3RM) of the pull-up (PU) was established in session 1. In session 2, rest periods for muscle enhancement of the upper body were determined using a medicine ball throw test 4, 8, and 12 minutes after UBPAP stimulus (1 × 3RM of the PU). In session 3, swimmers performed a countermovement jump 4, 8, and 12 minutes after LBPAP stimulus (1 × 5 jumps to a box while carrying 10% of the participants' body weight). The 50-m freestyle tests were performed on sessions 4-7, preceded by each warm-up protocol and corresponding rest periods. A repeated-measures analysis of variance (p = 0.05) and Bonferroni post hoc test revealed that RSWU elicited faster swimming times than UBPAP (29.00 ± 2.05 vs. 29.36 ± 1.88 seconds, p = 0.046). Additionally, when data were split into gender, in the male group, the UBPAP elicited significantly slower times than RSWU (27.51 ± 1.06 vs. 28.01 ± 1.17 seconds, p = 0.047) and CPAP (27.49 ± 1.12 vs. 28.01 ± 1.17 seconds, p = 0.02). These findings suggest individualized PAP warm-up may be a valuable tool to enhance performance in sprint events, particularly in male swimmers. However, the PU may not be an appropriate PAP stimulus on its own.